Focusky Application-Based Learning Media in the “Merdeka” Curriculum in Elementary Schools - Sutisna, Atang; Zaenal, Reza Muhamad; Nur’alim, Muhamad (Universitas Muhammadiyah Surakarta, 2023)
Curriculum changes in schools necessitate prompt responses, as they significantly impact the learning process. Within the framework of the “Merdeka” Curriculum, teachers must adopt a more creative approach to instruction. The development of Focusky-assisted learning media presents a viable alternative for implementing the “Merdeka” Curriculum in schools. This research employs a developmental methodology using the ADDIE model, with data collection techniques that include observation, interviews, and paired sample t-test analysis. The findings indicate that Focusky-based learning media was validated by subject matter experts and media specialists, achieving approval ratings of 95% and 88.9%, respectively. Additionally, the results from field testing demonstrated high practicality, with a rating of 81.8%. Furthermore, the average difference test, conducted to evaluate the effectiveness of student learning outcomes before and after the implementation of Focusky media, yielded a significance value of 0.000, which is less than the threshold of 0.05. These results conclusively demonstrate the effectiveness of Focusky-based learning media in enhancing student learning outcomes within the “Merdeka” Curriculum. The implications of this research underscore the potential of Focusky-assisted learning media to support teachers in delivering creative and innovative instruction. For students, this media is expected to facilitate more effective learning experiences.